Leaf elemental composition analysis in spider plant [Gynandropsis gynandra L. (Briq.)] differentiates three nutritional groups - Houdegbe, Aristide Carlos; Achigan-Dako, Enoch G.; Sogbohossou, E. O. Dêêdi; Schranz, M. Eric; Odindo, Alfred O.; Sibiya, Julia (Frontiers in Plant Science, 2022)
Understanding the genetic variability within a plant species is paramount in implementing a successful breeding program. Spider plant (Gynandropsis gynandra) is an orphan leafy vegetable and an extraordinary source of vitamins, secondary metabolites and minerals, representing an important resource for combatting malnutrition. However, an evaluation of the leaf elemental composition, using a worldwide germplasm collection to inform breeding programs and the species valorization in human nutrition is still lacking. The present study aimed to profile the leaf elemental composition of G. gynandra and depict any potential geographical signature using a collection of 70 advanced lines derived from accessions originating from Asia and Eastern, Southern and West Africa. The collection was grown in a greenhouse using a 9 × 8 alpha lattice design with two replications in 2020 and 2021. Inductively coupled plasma–optical emission spectrometry was used to profile nine minerals contents. A significant difference (p < 0.05) was observed among the lines for all nine minerals. Microelements such as iron, zinc, copper and manganese contents ranged from 12.59-430.72, 16.98-166.58, 19.04-955.71, 5.39-25.10 mg kg-1 dry weight, respectively, while the concentrations of macroelements such as potassium, calcium, phosphorus and magnesium varied in the ranges of 9992.27-49854.23, 8252.80-33681.21, 3633.55-14216.16, 2068.03-12475.60 mg kg-1 dry weight, respectively. Significant and positive correlations were observed between iron and zinc and calcium and magnesium. Zinc, calcium, phosphorus, copper, magnesium, and manganese represented landmark elements in the genotypes. East and Southern African genotypes were clustered together in group 1 with higher phosphorus, copper and zinc contents than Asian and West African lines, which clustered in group 2 and were characterized by higher calcium, magnesium and manganese contents. An additional outstanding group 3 of six genotypes was identified with high iron, zinc, magnesium, manganese and calcium contents and potential candidates for cultivar release. The genotype × year variance was greater than the genotypic variance, which might translate to phenotypic plasticity in the species. Broad-sense heritability ranged from low to high and was element-specific. The present results reveal the leaf minerals diversity in spider plant and represent a baseline for implementing a minerals-based breeding program for human nutrition.